Combined effect of laser irradiation and fluoride application in dental caries prevention - Sara Ghadimi; Mohammad Reza Khami; Samaneh Razeghi (Tehran University of Medical Sciences, 2015)
Background and Aims: Despite significant decline in dental caries in recent decades, the disease remains a public health problem especially in developing countries. In recent years combined application of laser and fluoride has been introduced as a new caries-preventive measure. The purpose of the present study was to review the literature on the preventive effect of combined application of laser and fluoride on the dental caries. Materials and Methods: PubMed, Google Scholar and EMBASE databases were searched for articles published from 1990 to November 30, 2013. Various combinations of the following keywords were used: Dental caries, Laser, Fluoride, Fluoride therapy, Prevention and Enamel. The inclusion criteria included all levels of available evidence. Articles published only in english language were evaluated, and unpublished data were not sought. Results: Several studies evaluating the effect of laser alone or combined with topical fluoride to prevent dental enamel demineralization were found. Studies assessing the combined effect were more frequently done on permanent teeth and just a few studies were done on primary teeth. In total, most of the studies confirmed that combined application of laser and topical fluoride has a remarkable effect in prevention of enamel demineralization compared to application of each of them alone. Conclusion: Laser irradiation combined with topical fluoride application seems to provide the best prevention effect on the dental caries initiation and progression in enamel of permanent teeth. However, more experimental and clinical studies are necessary to be done on the primary teeth in this area.